Central obesity increases risk of breast cancer irrespective of menopausal and hormonal receptor status in women of South Asian Ethnicity. (October 2016) - Nagrani, R.; Mhatre, S.; Rajaraman, P.; Soerjomataram, I.; Boffetta, P.; Gupta, S.; Parmar, V.; Badwe, R.; Dikshit, R.
Abstract: Background: Current evidence suggests that the relationship between obesity and breast cancer (BC) risk may vary between ethnic groups. Methods: A total of 1633 BC cases and 1504 controls were enrolled in hospital-based case–control study in Mumbai, India, from 2009 to 2013. Along with detailed questionnaire, we collected anthropometric measurements on all participants. We used unconditional logistic regression models to estimate odds ratios (ORs) and 95% confidence interval (CI) for BC risk associated with anthropometry measurements, stratified on tumour subtype and menopausal status. Results: Waist-to-hip ratio (WHR) of ≥0.95 was strongly associated with risk of BC compared to WHR ≤0.84 in both premenopausal (OR = 4.3; 95% CI: 2.9–6.3) and postmenopausal women (OR = 3.4; 95% CI: 2.4–4.8) after adjustment for body mass index (BMI). Premenopausal women with a BMI ≥30 were at lower risk compared to women with normal BMI (OR = 0.5; 95% CI: 0.4–0.8). A similar protective effect was observed in women who were postmenopausal for <10 years (OR = 0.6; 95% CI: 0.4–0.9) but not in women who were postmenopausal for ≥10 years (OR = 1.8; 95% CI: 1.1–3.3). Overweight and obese women (BMI: 25–29.9 and ≥ 30 kg/m 2, respectively) were at increased BC risk irrespective of menopausal status if their WHR ≥0.95. Central obesity (measured in terms of WC and WHR) increased the risk of both premenopausal and postmenopausal BCs irrespective of hormone receptor (HR) status. Conclusions: Central obesity appears to be a key risk factor for BC irrespective of menopausal or HR status in Indian women with no history of hormone replacement therapy. Highlights: Waist-to-hip ratio increases risk of breast cancer (BC) irrespective of menopausal or hormone receptor status. High body mass index (BMI) protects the risk of BC in premenopausal women. The protection in risk of BC continues in women who have high BMI and are postmenopausal for <10 years. There is an increase in risk of BC in women have high BMI and are postmenopausal for ≥10 years.